Factors Affecting the Surface Roughness in Sinking EDM Process - Ahmad Atif Fikri; Maftuchin Romlie; Aminnudin Aminnudin (Journal of Mechanical Engineering Science and Technology (JMEST), 2017)
The purpose of this study is to gain insights into the surface quality (smoothness) of sinking EDM machining products. Among other non- conventional machining processes, Electrical Discharge Machining (EDM) is the most commonly used process. EDM is a machining process that uses electric sparks created between a workpiece and a tool (electrode). As a manufacturing process, EDM is used for workpieces which have intricate contours and precise dimensions, and works by using electric discharges (sparks) applied in a rapid series of repetitive electrical discharges between the two electrodes, separated by a dielectric fluid, and subject to an electric voltage. Since the tool tends to wear easily and the mould material is very hard and tough, it is necessary to keep within appropriate EDM machining parameters, so that the smoothness of the mould lives up to expectations. Therefore, the parameters of sinking EDM process should be well established to produce the expected results, i.e. the smoothest surface quality and the maximum removal rate. Regarding the electrode materials used, conducting a further experiment is required to achieve the appropriate settings of pulse current, on-time, off-time, servo voltage, and gap width. This experimental study involved several factors: (a) electrode material, (b) magnitude of current, (c) on-time, and (d) quality of surface (smoothness). In this study, the gap between the electrode and the workpiece was controlled at a distance of 40 μm, and with an off-time of 5 seconds, the same dielectric fluid, the same flow speed and the same dielectric immersion, and using the workpiece (AISI P20M steel). Quantitative approaches (t test, one-way, and ANOVA) were applied to analyse the results of comparison test and to determine the best parameter in sinking EDM process.